Grafeno epitaxial sobre sic(0001): crescimento, intercalação e efeitos de interface - Igor de Souza Lana Antoniazzi (2019)
In this work we investigate the influence of the graphene-substrate interface on the electronic properties of quasi-free-standing (QFS) bilayer graphene grown on silicon carbide (SiC). The QFS bilayers were developed by intercalating hydrogen and oxygen atoms between the buffer-layer and the SiC interface. In the first part of the work we have constructed a system dedicated to the growth of epitaxial graphene by decomposition of the SiC surface. The system is composed of a quartz tube chamber, which operates in the range of 1 x 10-5 - 1 x 103 mbar, and contains a resistive heating unit. It works at high temperatures, reaching up to 1800 ºC, and allows a precise control of the growth atmosphere composition and gas flow. After the structural characterization of the monolayer graphene samples prepared using this homemade system, samples were intercalated using hydrogen and oxygen. Structural quality of the QFS bilayers were investigated by Raman scattering spectroscopy and scanning tunneling microscopy, which reveled that oxygen intercalated samples offer lower structural quality compared to the H intercalated ones. Due to the intrinsic high doping level of the QFS bilayers, it was necessary to develop a device that could lead to a high carriers density, allowing us to perform electrical measurements near to the graphene neutrality point. Thus, instead of using solid top gate dielectric, we prepared an electrochemical top gate using an ion gel. However, even though gap-like structures could be observed in the STS spectra, this result could not be confirmed by electrical measurements.